Crossed testicular ectopia: Report of six cases - Melih Akin; Başak Erginel; Salim Bilici; Şenol Gedik; Abdullah Yıldız; Çetin Ali Karadağ; Nihat Sever; Ali İhsan Dokucu (Wolters Kluwer Medknow Publications, 2014)
Crossed testicular ectopia or transverse testicular ectopia is an extremely rare anomaly characterised by migration of one testis towards the opposite inguinal canal, usually associated with unilateral inguinal hernia. This report describes six cases of crossed ectopic testes, one of the largest series, and with unusual clinical histories.